1999
DOI: 10.1007/978-1-4612-1554-7
|View full text |Cite
|
Sign up to set email alerts
|

Subsampling

Abstract: cm. -(Springer series in statistics) lncludes bibiiographicai references and index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
965
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 942 publications
(976 citation statements)
references
References 0 publications
9
965
0
2
Order By: Relevance
“…A number of avenues of potential future work remain. For example, it would be interesting to apply our diagnostic procedure to other estimator quality assessment methods [4,17,13] and to devise extensions of the diagnostic which are suitable for variants of the bootstrap designed to handle non-i.i.d. data [9,12,14,16,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of avenues of potential future work remain. For example, it would be interesting to apply our diagnostic procedure to other estimator quality assessment methods [4,17,13] and to devise extensions of the diagnostic which are suitable for variants of the bootstrap designed to handle non-i.i.d. data [9,12,14,16,18].…”
Section: Resultsmentioning
confidence: 99%
“…Unlike classical methods-which have generally relied upon analytic asymptotic approximations requiring deep analysis of specific classes of estimators in specific settings [17]-the bootstrap can be straightforwardly applied, via a simple computational mechanism, to a broad range of estimators. Since its inception, theoretical work has shown that the bootstrap is broadly consistent [3,10,20] and can be higher-order correct [11].…”
Section: Introductionmentioning
confidence: 99%
“…Politis et al (1999) study uniform confidence bands for marginal distributions of stationary time series (example 3.4.7 page 89), and discuss ways to generalize bootstrap procedures to the nonstationary case (Section 4.4). A thorough review of bootstrap methods in time series is given in Haerdle et al (2003), which notes a number of shortcomings of resampling methods under dependency.…”
Section: Uncertainty Assessmentmentioning
confidence: 99%
“…, X i+b−1 ). Generalizations for nonstationary time series, random fields and point processes are further discussed in Politis et al (1999).…”
Section: A Subsampling Approachmentioning
confidence: 99%